A critique of utilitarian and instrumentalist concepts for the teaching of gross anatomy to medical and dental students: Provoking debate - Moxham, Bernard J.; Pais, Diogo (Clinical anatomy (New York, N.Y.), 2017)
Medical and dental curricula, together with anatomical sciences courses, are increasingly having to change, mainly because there is a drive to being what is termed, without adequate definition, “clinically relevant.” The concept of “clinical anatomy” has accordingly been invented and it is expected that, at all times, the teaching of anatomy is directly focused on clinical scenarios, meaning almost invariably the disease‐based model of medicine and dentistry. Furthermore, students are not expected to have a detailed knowledge of gross anatomy and the time devoted to teaching and learning the subject has decreased significantly. The notion being fostered is that knowledge is not required “just in case” but “just in time.” However, the absence of agreed core syllabuses that are internationally accepted complicates a discussion about what is relevant practically and what does not need to be taught. In this article, we critique such an utilitarian and instrumentalist approach to the teaching of gross anatomy within medical and dental curricula. We draw attention to the need to embrace the functionality‐based model of medicine and dentistry by returning to an understanding that the role of the medical or dental practitioner is to value health and to restore to functionality the ill person or the pathologically affected region/organ/system. A fuller knowledge of anatomy than is presently taught is regarded as a prerequisite for appreciating normality and health. A further problem with the instrumentalist approach to medical education is that, by concentrating on what is seen to be at the time “useful” or “clinically relevant,” there is the danger of undermining, or discouraging, future developments that rely on what contemporaneously seems “useless” and “irrelevant” knowledge. Finally, the reliance instrumentalism has on just what is pragmatic and regardless of scientific validity is contrary to the ethos and practice of a university education that values deep learning and the development of learnèd professions. Clin. Anat. 30:912–921, 2017. © 2017 Wiley Periodicals, Inc.